2010
DOI: 10.1016/j.proeng.2010.04.094
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for monitoring clubhead path and orientation through impact

Abstract: This study reports the development of a golf clubhead trajectory monitoring system which utilises PONTOS, a 3D motion analysis package from GOM. This paper demonstrates how this system can be used to monitor clubhead path and orientation and position throughout impact with future scope to simultaneously measure ball launch conditions. Six subjects performed 10 swings with a driver and a selection of these shots were analysed in detail. Face angle and dynamic loft were calculated as indicators of clubhead orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…After the impact, the clubface tends to open when the ball contacts the clubface in the toe region. The DL tends to decrease after the impact at the centre or low on the clubface, which is in accordance with other results based on the video monitoring system (Ellis, Roberts, & Sanghera, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…After the impact, the clubface tends to open when the ball contacts the clubface in the toe region. The DL tends to decrease after the impact at the centre or low on the clubface, which is in accordance with other results based on the video monitoring system (Ellis, Roberts, & Sanghera, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This trend may be a legacy of the development process as early versions of each launch monitor only reported ball parameters and clubhead measurement was introduced at a later data Weaker agreement was found when clubhead velocity measured by both launch monitors was compared to the GOM measurements; greater systematic bias and random variability was present in the data, particularly when considered relative to the ball velocity data. Immediately before impact, the clubhead is both translating and rotating and, as a result, velocity can vary by as much as 12.8 mph from heel to toe across a driver clubface [7]. Differences are, therefore, to be expected depending on where on the clubhead the velocity measurement is taken.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, velocity of a point on the surface of the clubhead is measured and this may account for discrepancies in the data Clubhead orientation parameters can change rapidly leading up to impact due to clubhead rotations primarily about the shaft axis. The face angle of a driver closes at a rate of 2.9º/ms immediately prior to impact [7]. Therefore, the point in time at which the measurement is taken will significantly affect the output from the launch monitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is reasonable that club-head velocity should indeed play a large part in generating ball velocity, it has also been suggested that the location of impact relative to the center of the clubface would also contribute to the ball velocity (Hocknell, 2002;Wiren, 1990). Quantitatively, researchers have established that the location of impact on the club-face has a large effect on club-head orientation, path, and velocity following impact (Ellis, Roberts, & Sanghera, 2010;Williams & Sih, 2002). However, there is currently a lack of understanding of the relative contribution of both club-head velocity and impact location on ball velocity.…”
Section: Introductionmentioning
confidence: 99%